Volumetric Properties in the NaAsO2 + H2O System at Temperature from 283.15 to 363.15 K and Atmospheric Pressure - Hongfang Hou; Wanjing Cui; Jiaojiao Chen; Lingzong Meng; Yafei Guo; Tianlong Deng (Journal of Chemistry)
Densities of sodium arsenite (NaAsO2) aqueous solution with the molality varied from 0.19570 to 1.94236 mol·kg−1 at temperature intervals of 5 K from 283.15 to 363.15 K and 101 ± 5 kPa were measured by a precise Anton Paar Digital vibrating-tube densimeter. Apparent molar volumes (VΦ) and thermal expansion coefficient (α) were obtained on the basis of experimental data. The 3D diagram of apparent molar volume against temperature and molality and the diagram of thermal expansion coefficient against molality were generated. According to the Pitzer ion-interaction equation of the apparent molar volume model, the Pitzer single-salt parameters (βM,X0υ, βM,X1υ, βM,X2υ, and CM,Xυ, MX = NaAsO2) and their temperature-dependent correlation F(i, p, T) = a1 + a2ln (T/298.15) + a3(T − 298.15) + a4/(620 − T) + a5/(T − 227) (where T is temperature in Kelvin and ai are the correlation coefficients) for NaAsO2 were obtained for the first time. The predictive apparent molar volumes agree well with the experimental values, and those results indicated that the single-salt parameters and the temperature-dependent formula are reliable.